The Relationship between Education and the Public Library in Turkey - Dalkıran, Ömer (Information World, 2014)
Education; individuals is a process aimed at creating the desired behavior. Education not only in school, and in all areas of life takes place in a variety of ways. Libraries, especially public libraries is an integral part of education. One of the main functions of public libraries is education. A close relationship between education and the public library is located. This relationship is often discussed in theoretical level. In this study, this relationship was tried to be put forward concrete indicators. In this context, education and public libraries in Turkey between the years of 1950-2011 mutually statistics are evaluated. Thus, the public library of education in Turkey and aimed to find out whether there was a relationship. According to the findings, and the public library of general education in Turkey felt in certain periods, especially a relationship that may be mentioned. However, this relationship does not show the regularity and continuity.